Lactobacillus casei Ghosts as a Vehicle for the Delivery of DNA Vaccines Mediate Immune Responses - Yu, Xiaoli; Wang, Li; Yang, Xinru; Zhang, Songsong; Li, Guiwei; Zhang, Lanlan; Li, Jiaxuan; Wang, Xiaona; Zhou, Han; Jiang, Yanping; Cui, Wen; Li, Yijing; et al. (Frontiers in Immunology, 2022)
We developed Lactobacillus casei bacterial ghosts (BGs) as vehicles for delivering DNA vaccines and analyzed their effects on immune responses. Uptake of the plasmids encoding the enhanced green fluorescent protein (pCI-EGFP) and BGs loaded with pCI-EGFP by macrophages was investigated using fluorescence microscopy and flow cytometry. The results showed that pCI-EGFP-loaded L. casei BGs were efficiently taken up by macrophages. Lactobacillus casei BGs loaded with plasmids encoding VP6 protein of PoRV (pCI-PoRV-VP6) significantly upregulated the mRNA expression of interleukin (IL)-1β, IL-10, tumor necrosis factor (TNF)-α, inducible nitric oxide synthase (iNOS), arginase-1 (Arg-1), Mannose receptor (CD206) toll-like receptor (TLR)-2, TLR4, and TLR9 in macrophages. The levels of markers of M1 polarization (IL-10 and TNF-α) and M2 polarization (Arg-1 and CD206) were increased in macrophages incubated with pCI-PoRV-VP6-loaded BGs compared with the control group. The results of the enzyme-linked immunosorbent assay showed that the secretion of IL-1β, IL-10, and TNF-α in macrophages was significantly upregulated compared with the control group. Flow cytometry demonstrated that L. casei BGs loaded with pCI-PoRV-VP6 promoted the maturation of dendritic cells (DCs). Following incubation with pCI-PoRV-VP6-loaded BGs, the mRNA expression levels of IL-1β, IL-6 and interferon (IFN)-γ in DCs were significantly increased. ELISA assay showed the secretion of the IL-1β, IL-6, IFN-γ IL-10 and TNF-α in DCs were upregulated significantly. Thus, L. casei BGs promoted the maturation and activation of DCs. We analyzed the stimulatory capacity of DCs in a mixed lymphocyte reaction with allogeneic T cells. T cell proliferation increased upon incubation with DCs stimulated by BGs. After immunizing mice with BGs loaded with pCI-PoRV-VP6, the specific IgG levels in the serum were higher than those elicited by BGs loaded with pCI-PoRV-VP6. BGs loaded with pCI-PoRV-VP6 on Th1 and Th2 cytokines polarized T cells into the Th1 type and increased the proportion of CD4+/CD8+ T cells. These results indicate L. casei BGs effectively mediate immune responses and can be used as delivery system for DNA vaccination.